Santripreneur Berdaya: Inkubasi Bisnis Berbasis Nilai Keislaman di Lingkungan Pesantren Ribatul Muta’allimin - Arif Pujiyono; Evi Yulia Purwanti; Putri Rizka Citaningati; Maal Naylah; Wahyu Widodo (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
This community service program aims to develop the entrepreneurial capacity of Islamic boarding school students through an Islamic-based business incubation model at the Ribatul Muta'allimin Islamic Boarding School. The main problems faced include low entrepreneurial literacy, lack of practical business skills, and the suboptimal integration of Islamic economic values ​​into business practices. The implementation method uses a participatory approach through training, hands-on practice (learning by doing), and ongoing business mentoring. This program also integrates Islamic values ​​at every stage, resulting in santripreneurs who are not only economically competent but also ethical. The expected results are the formation of santri business units, increased entrepreneurial skills, and the development of a sustainable Islamic boarding school-based business ecosystem. This program is expected to become a model for Islamic boarding school economic empowerment that can be replicated in various regions.